1995
DOI: 10.1111/j.1464-5491.1995.tb02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth and Insulin Resistance in Adult Life: Role of Plasma Triglyceride and Non‐esterified Fatty Acids

Abstract: Reduced fetal growth is associated with insulin resistance and a high prevalence of glucose intolerance in adult life. Because babies who are growth retarded have elevated levels of triglyceride and non-esterified fatty acids (NEFA), and because similar abnormalities are observed in subjects with the insulin resistance syndrome, impaired regulation of lipid metabolism could be one of the mechanisms explaining the link between reduced fetal growth and insulin resistance. We have, therefore, measured fasting pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 28 publications
(3 reference statements)
0
12
0
1
Order By: Relevance
“…Some 3,4,7 but not all 5,11,14 previous studies that have examined the relationship between birth weight and waist -hip ratio have found a small inverse association after adjustment for current body size. Law et al 3 interpreted this association as evidence of a link between fetal growth and abdominal fatness.…”
Section: Discussionmentioning
confidence: 99%
“…Some 3,4,7 but not all 5,11,14 previous studies that have examined the relationship between birth weight and waist -hip ratio have found a small inverse association after adjustment for current body size. Law et al 3 interpreted this association as evidence of a link between fetal growth and abdominal fatness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, also it has been reported that conditions that modify insulin concentration during fetal life could alter the normal development of endocrine system, predisposing to insulin resistance in adult life [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…An association with only one of the we failed to observe associations between birth weight and NEFA suppression during an OGTT or between birth established features without an association with insulin resistance would lessen the strength of inference that a weight and fasting NEFA concentrations. 30 Although increased central adiposity has previously been linked variable should be included as a novel feature of the syndrome. In conclusion, we suggest that insulin with low birth weight in both men and women 31 our result needs repeating in a larger study.…”
mentioning
confidence: 99%